2022
DOI: 10.1002/ece3.9374
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the distribution of plant associations under climate change: A case study on Larix gmelinii in China

Abstract: Association is the basic unit of plant community classification. Exploring the distribution of plant associations can help improve our understanding of biodiversity conservation. Different associations depend on different habitats and studying the association level is important for ecological restoration, regional ecological protection, regulating the ecological balance, and maintaining biodiversity. However, previous studies have only focused on suitable distribution areas for species and not on the distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 114 publications
(135 reference statements)
0
0
0
Order By: Relevance
“…Our results showed that the future distribution of the highly suitable area for coniferous species (L. gmelinii) is projected to shrink primarily in Northeast China, while evergreen broad-leaved tree species (S. superba and C. officinarum) will tend to expand towards the central regions of China from 2015 to 2060 based on the MaxEnt model. Similar conclusions have also been reported, for example, by Bai et al (2016) and Chen et al (2022) [40,41], who found, through research on the relationship between tree rings and temperature changes, that rapid warming will lead to the gradual decline of L. gmelinii in Northeast China. Du et al (2022) [42] found that the future suitable habitat area of eight species of tree species in the Northeast region, including L. gmelinii, will decrease by 10%-30%.…”
Section: Discussionsupporting
confidence: 88%
“…Our results showed that the future distribution of the highly suitable area for coniferous species (L. gmelinii) is projected to shrink primarily in Northeast China, while evergreen broad-leaved tree species (S. superba and C. officinarum) will tend to expand towards the central regions of China from 2015 to 2060 based on the MaxEnt model. Similar conclusions have also been reported, for example, by Bai et al (2016) and Chen et al (2022) [40,41], who found, through research on the relationship between tree rings and temperature changes, that rapid warming will lead to the gradual decline of L. gmelinii in Northeast China. Du et al (2022) [42] found that the future suitable habitat area of eight species of tree species in the Northeast region, including L. gmelinii, will decrease by 10%-30%.…”
Section: Discussionsupporting
confidence: 88%
“…The precision of the MaxEnt model in predicting species spatial distribution is not significantly affected by the sample size [24]. It performed excellently in terms of its simulation performance, either in the suitability research on Larix gmelinii among the 182 current distribution points or in a study on species suitable distribution areas of Picea smithiana (Pinaceae: Picea) at the extremely low sample size (n = 28) among the current distribution points, further demonstrating that the MaxEnt model well predicted the distribution patterns of rare species [15,25]. Xiao et al [26] employed the MaxEnt and genetic algorithm for rule-set production (GARP) models to predict the suitable distribution area of Procambarus clarkii, finding that the prediction results by MaxEnt were more accurate.…”
Section: Introductionmentioning
confidence: 81%